Influência das estações do ano na composição e qualidade sanitária do leite bovino de Valle de Lerma, Salta - MARTINEZ, Gabriela M. (Universidad Nacional del Litoral, 2020)
The aim of this study was to determine the seasonal influence in bovine milk composition and sanitary quality for Lerma Valley basin. Samples sent by dairy industries to National University of Salta Milk Laboratory during spring (Pr, n: 104), summer (Ve, n: 131) and winter (In, n: 118) of the years 2017 and 2019 were analyzed. Fat (% F) and protein (% P) percentages, freezing point (FP) and somatic cell count / ml (RCS / ml) were determined. Statistical analysis was performed using the InfoStat 2019p program. The model responded to a CRD. % F and % P were analyzed by ANOVA, while for FP and SCC  non-parametric ANOVA from Kruskal Wallis was used. Tukey Test (p <0.05) was used for means comparasions. % F was according to Argentine legislation in all seasons of the year, although ln value was lower than that  Su (3.49  vs. 3.64, p= 0.0009). % P was similar in the 3 stations, but below the national standards (Wi: 3.24, Sp: 3.26, Su: 3.26). FP (° C), differed between Wi (-0.522) and Sp (-0.519) and Su (-0.518) (p=0,0023), although values were below the upper range value. SCC (cel / ml) Wi In and Sp was similar (264000 vs. 228000 cel/ml, respectively), while in Su it was higher (p = 0.0012) showing higher average values (430,000 cel / ml) than the limit established by national standards. The results obtained in this study were accord with the chemical and sanitary composition of reference in Argentina, except for protein levels and SCC during the summer.